A systematic review on considering the role of Magnesium in preventing post-anesthesia shivering: Role of Magnesium in preventing post-anesthesia shivering - Zhu, Hua; Zhou, Wen; Chen, Yijian (Cellular and Molecular Biology, 2022)
Shivering following anesthesia is caused by disturbed regulation of body temperature and causes an increase in tissue oxygen consumption and cardio-pulmonary activity. Choosing the right medicine to reduce shivering with the most negligible side effects in surgery is essential. Magnesium is prescribed intravenously, epidurally, or intra-peritoneally. Each of these methods can have different effects in different surgical operations. In this review, we are looking for randomized clinical trials that compared preoperative magnesium administration with a control group and included studies that evaluated the degree of shivering as a primary outcome variable. This study aimed to evaluate pre-operative magnesium’s effect in preventing shivering after surgery. This article was a systematic review type, in which all quality articles published until the end of 2021 were searched with the keywords magnesium, shivering, surgery, and prevention via different databases, including PubMed, Cochrane Central Register of Tested Controlled, EMBASE and Web of Science. In the initial search, 3294 publications were identified. 64 articles were included in this study. The results indicated that shivering in the magnesium group with IV epidural injection inside the peritoneum was significantly reduced compared to the control group. It was also identified in the examination of symptoms. Variants such as extubation time, length of stay in PACU, magnesium serum concentration, spinal c-fos mRNA expression, nausea or vomiting, sedation, itching, pressure drop, and bradycardia were significantly less reported than the control group. In general, the results showed that the preventive use of magnesium could decrease the intensity and number of post-anesthesia shivering and other post-anesthesia symptoms.